Laterality in laparoscopic hand assisted donor nephrectomy - Does it matter anymore? Outcomes of a large retrospective series. Issue 5 (October 2022) - Vaz, Osborne; Asderakis, Argiris; Sharma, Videha; Moinuddin, Zia; Shanmugam, Mohan; Tavakoli, Afshin; van Dellen, David; Augustine, Titus
Abstract: This retrospective study was performed to analyse if laterality of the retrieved living donor kidney had any effect on donor and recipient outcomes after hand assisted laparoscopic donor nephrectomy (HALDN). 739 donors who underwent HALDN between January 2006 and January 2018 at a large tertiary transplant centre in the United Kingdom were included. Donor outcomes in individuals undergoing right versus left HALDN were compared with respect to conversion rates, morbidity, warm and cold ischaemia times and recipient failure rates, vascular and ureteric complications. 604 (81.7%) underwent left HALDN and 135 (18.3%) underwent right HALDN, mean age was 47.1 years and 46.8 years respectively with comparable gender distribution. The operative time was shorter for the left side (p = 0.003) and improved during the study for the left but not the right side. In recipients who received left kidneys there were more early technical failures observed (8 versus 1) though not statistically significant. Most centres prefer performing a left nephrectomy and recipient surgeons prefer a left kidney for transplantation primarily because of having a longer vein. This large study provides reassurance that right HALDN nephrectomy is a safe procedure with similar outcomes to left HALDN. Highlights: Kidney transplantation remains the most optimal renal replacement modality. This large study provides reassurance that right HALDN nephrectomy is a safe procedure. Right HALDN should be offered when clinically indicated. There are no significant differences in donor and recipient outcomes between right and left HALDN.